Lichen sclerosus. - Garofalo, L. (European Journal of Pediatric Dermatology, 2015)
Lichen sclerosus prevails in the female, especially before puberty and after menopause (2), suggesting the importance of hormonal factors.The same factors may be responsible for the significant improvement of the lesions in the peripubertal period as observed in the majority of childhood cases. Moreover, the importance of the gene factors is suggested by the familial cases (1, 2). In the family and personal history of patients with lichen sclerosus there are often autoimmune disease; in this particular case the mother of the patient was suffering from erosive lichen of the tongue and in her family there were numerous cases of autoimmune thyroiditis. The vulvar and perianal lesions, which are more frequently symptomatic, respond well to the topical immunosuppressive therapy, preferably tacrolimus. It is also useful to avoid sports such as cycling which traumatise the vulvar region.